Akkadian Chrestomathy - Böhl, F. M. Th. (1947)
Assyrian Royal Inscriptions; Accadian and Babylonian Inscriptions; Chronicles and Cyrus О Inscription; Epical Texts; Hymns, Psalms, Ritual and Magical Texts; Babylonian Letters and Business Documents; Letters and Treaties from Mari, El-Amarna and Boğazköy; Doll. 7.